Damage analysis of out of plane undulated fiber composites. (15th September 2016) - Eskandari, Sina; Andrade Pires, F.M.; Camanho, P.P.; Marques, A.T.
Abstract: It is very important to widen the design capacity by analyzing different configurations of composite materials. Out of plane undulated fiber composite is one category of the variable stiffness composites which has attracted research community attention. Waved fibers in this type can be as an unintentional result of production process or a deliberate design purpose. In this research, a 3 dimensional constitutive model is proposed for continuum damage analysis of through thickness curvilinear fiber composites. Larc failure criteria is used in order to determine the damage onset which is a well-established criteria for composite structures. The model is developed by 2 different approaches. In the first approach, it is assumed that the wave shape is fixed during the analysis, while in the second one the geometrical non-linearity is taken into account. Damage evolution is based on the Maimi continuum damage model. Several numerical examples are implemented and results are compared together and the experimental data. There is a good agreement between the second approach and the experiments. Finally a parametric study is conducted and the results are reported.